The Rocky Road to Publishing in the Management and Decision Sciences and Beyond Experiencing the Journey and Lessons Learned - Korhonen, Pekka; Moskowitz, Herbert; Wallenius, Jyrki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book documents the history of two research papers, from the first drafts to the final polished published articles, including the reviewer comments and the author responses. The documentary provides unique insights into the publishing process, which at times is filled with uncertainties, not only for young researchers. The book discusses lessons learned and also provides an experienced editor's and reviewer's perspective. In the light of the high pressure on young faculty to publish successfully, this book offers itself as a guide to publishing efficiently and effectively in a highly competitive scientific environment.
Part 1: Prologue -- Part 2: Case Study 1 (Choice Behaviour in Interactive MCDM: A Rocky road) -- Part 3: Case Study 2 (Can a Linear Value Function Explain Choices? An Experimental Study: A Not So Rocky Road) -- Part 4: Epilogue.
Keywords: Economics; Operations research; Economics/Management Science; Operation Research/Decision Theory; Operations Research, Management Science; Business/Management Science, general